Analysis of preparation of financial statements based on Sak Etap - Selvi Aristantya (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the arrangement of financial statements which were applied by the Maju Bersama Cooperative as the entity engaged in savings and loans. The discussion was done by comparing between a theory proposed by IAI about Financial Accounting Standards for Entities without Public Accountability (SAK ETAP) and the implementation in Maju Bersama Cooperatives, also recommending some improvements toward the arrangement of financial statements in Maju Bersama Cooperatives based on SAK ETAP. This study used descriptive qualitative method with a case study approach. The purpose is to describe systematically about the focus of the study. The result of the study shows that in the process of implementing the existing accounting cycle, the Maju Bersama Cooperative did not record transactions in the journal entry, and journal entries to the posting ledger based on SAK ETAP and the accounting cycle in general. Cooperation only came on the recapitalization stage which is a trial balance and financial statement. In the implementation of arranging the financial statement done by the Maju Bersama Cooperative in 2018 it was not suitable with SAK ETAP because the financial statement was only in the form of a balance, and a gain-loss report.